Ranging behavior of female and male Shiny Cowbirds and Screaming Cowbirds while searching for host nests. (13th August 2014) - Scardamaglia, Romina C.; Reboreda, Juan C.
Abstract: Brood-parasitic cowbirds are hypothesized to search for and locate host nests within a relatively constant area, as this is presumed to facilitate the monitoring of nests over time and the synchronization of parasitism with host laying. We tested this hypothesis in Shiny Cowbirds ( Molothrus bonariensis ) and Screaming Cowbirds ( M. rufoaxillaris ), two cowbird species that differ in host specificity and, apparently, in social mating system, by radio-tracking females and males for 3–6 consecutive days and determining individual daily morning ranges and cumulative morning ranges. In Shiny Cowbirds, the mean size of morning daily ranges and cumulative morning ranges was larger for males than for females, but we did not find a difference between the sexes in range size for Screaming Cowbirds. In both species, there was extensive overlap in the morning ranges of individual females between consecutive days, and the addition of new area to their ranges decreased over time. For both Shiny and Screaming cowbirds, morning ranges of conspecific females radio-tracked the same day overlapped, indicating lack of territoriality. Male and female Screaming Cowbirds that were trapped together were also spatially associated during radio-tracking, indicating social monogamy. Most radio-tracked Shiny and Screaming cowbirds used mainly one roost, relatively close to their morning ranges, which was maintained throughout the breeding season. Our results show that Shiny and Screaming cowbird females use relatively constant areas for nest searching and that Screaming Cowbirds are socially monogamous.